Interictal, circulating sphingolipids in women with episodic migraine: A case-control study. (6th October 2015) - Peterlin, B. Lee; Mielke, Michelle M.; Dickens, Alex M.; Chatterjee, Subroto; Dash, Paul; Alexander, Guillermo; Vieira, Rebeca V.A.; Bandaru, Veera Venkata Ratnam; Dorskind, Joelle M.; Tietjen, Gretchen E.; Haughey, Norman H.
Abstract : Objective: To evaluate interictal, circulating sphingolipids in women migraineurs. Methods: In the fasting state, serum samples were obtained pain-free from 88 women with episodic migraine (EM; n = 52) and from controls (n = 36). Sphingolipids were detected and quantified by high-performance liquid chromatography coupled with tandem mass spectrometry using multiple reaction monitoring. Multivariate logistic regression was used to examine the association between serum sphingolipids and EM odds. A recursive partitioning decision tree based on the serum concentrations of 10 sphingolipids was used to determine the presence or absence of EM in a subset of participants. Results: Total ceramide (EM 6, 502.9 ng/mL vs controls 10, 518.5 ng/mL; p < 0.0001) and dihydroceramide (EM 39.3 ng/mL vs controls 63.1 ng/mL; p < 0.0001) levels were decreased in those with EM as compared with controls. Using multivariate logistic regression, each SD increase in total ceramide (odds ratio [OR] 0.07; 95% confidence interval [CI]: 0.02, 0.22; p < 0.001) and total dihydroceramide (OR 0.05; 95% CI: 0.01, 0.21; p < 0.001) levels was associated with more than 92% reduced odds of migraine. Although crude sphingomyelin levels were not different in EM compared with controls, after adjustments, every SD increase in the sphingomyelin species C18:0 (OR 4.28; 95% CI: 1.87, 9.81; p = 0.001) and C18:1 (OR 2.93; 95% CI: 1.55, 5.54; p = 0.001) was associated with an increased odds of migraine. Recursive portioning models correctly classified 14 of 14 randomly selected participants as EM or control. Conclusion: These results suggest that sphingolipid metabolism is altered in women with EM and that serum sphingolipid panels may have potential to differentiate EM presence or absence. Classification of evidence: This study provides Class III evidence that serum sphingolipid panels accurately distinguish women with migraine from women without migraine.